2002
DOI: 10.1103/physrevc.65.044316
|View full text |Cite
|
Sign up to set email alerts
|

Regular spectra in the vibron model with random interactions

Abstract: The phenomenom of emerging regular spectral features from random interactions is addressed in the context of the vibron model. A mean-field analysis links different regions of the parameter space with definite geometric shapes. The results that are, to a large extent, obtained in closed analytic form, provide a clear and transparent interpretation of the high degree of order that has been observed in numerical studies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 27 publications
6
30
0
Order By: Relevance
“…For this reason, the Hamiltonian effectively depends on two random coefficients cos χ and sin χ , which can be either attractive or repulsive. The distribution of ground state angular momenta was obtained exactly in a mean-field study [17]. For even values of the number of bosons N , the ground state has v = 0 in 75% of the cases and v = N in the remaining 25 %.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the Hamiltonian effectively depends on two random coefficients cos χ and sin χ , which can be either attractive or repulsive. The distribution of ground state angular momenta was obtained exactly in a mean-field study [17]. For even values of the number of bosons N , the ground state has v = 0 in 75% of the cases and v = N in the remaining 25 %.…”
Section: Resultsmentioning
confidence: 99%
“…(5) has a spherical ground state for sin χ | cos χ | and a deformed one for sin χ | cos χ | [17,21]. In the first case, the appropriate basis is that of the U (5) limit of the IBM, |N, n, v .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When one applies the TBRE Hamiltonian to sp bosons [51,52], sd bosons [16,17,51,53,54,55,56,57], and sdg [58] bosons (we shall come to these cases in subsections 4.6 and 5.2), the 0 g.s. dominance is found also for an odd number of bosons.…”
Section: Bosons With Spin Lmentioning
confidence: 99%
“…Group theory was used to show that the TBRE on a single j shell had a particular group symmetry and "this gave rise to the simplicity in the ground state structures" [16]. A Hartree-Fock calculation in the IBM and vibron model showed that there are 3 equilibrium shapes that explain the rotational bands and J0D [6,17,18]. An expression for the energy gap in the lowest spin states in the TBRE was found in [19].…”
Section: Explanationsmentioning
confidence: 99%